Composition and Antibacterial Activity of the Volatile Oils from Different Parts of Achillea tenuifolia Lam. from Iran - A Shafaghat (Institue of Medicinal Plants, ACECR, 2009)
Background: Achillea tenuifolia Lam. (Compositae) with small yellow flowers and several times pinnately divided leaves in worm shape is known for many years in the folk medicine. It has been used to reduce sweating and to stop bleeding. It helps regulation of the menstrual cycle and reduces heavy bleeding and pain. Materials and Methods: Plant material (flower, leaf and stem) was collected in Khalkhal - Ardabil road area, at an altitude of 1650 m in Northwest of Iran. Plant materials were air dried 150g of flower 150g of leaf and 200g of stem were subjected to 3h of hydrodistillation in a Clevenger-type apparatus, separately. The hydrodistilled essential oils were analyzed by GC and GC/MS methods. Antibacterial activities of the oils were evaluated by the disc diffusion method using Mueller-Hinton agar for bacteria. Results: The oil of flower was characterized by higher amount of limonene (23.2%) and α-cadinol (18.2%). Twenty one constituents representing (92.2%) of the leaf oil were identified of which limonene (25.2%), α- pinene (14.4%), caryophyllene oxide (6.5%), α- gurjunene (6.3%), bornyl acetate (5.5%) and δ-cadinene (4.4%) were major components. The main components of the stem oil were limonene (23.6%), α- pinene (13.4%) and spathulenol (6.4%). The oils showed inhibitory effects on Escherichia coli and Salmonella typhi. Conclusions: The main components of the oil of flower, leaf and stem were limonene, α-cadinol, α- pinene and spathulenol, but Borneol, bornyl acetate, camphor, α- and β-thujone, and 1, 8-cineol were found as the main components of essential oils of many other Achillea species. These variations may be attributed mainly to variation in their agroclimatic and geographical conditions. The results indicated that three oils were found to be active against bacteria, the oil from the flower was found to be more active than the oil from the leaf and stem.